Pathogen responses in foods : underestimated ecophysiological factors - Dourou, Dimitra (Cranfield University, 2009)
Accurate prediction of the fate of microbial foodborne pathogens in foods is of great concern for anyone involved in the food chain. Factors that may influence microbial responses in foods and food environments, such as food structure and composition, microbial interactions and mode of growth were identified and assessed in the present study. The fate of Listeria monocytogenes, Salmonella Typhimurium and Escherichia coli O157:H7 was monitored both in and on teewurst, a raw spreadable sausage, at different storage temperatures. Regardless of the storage temperature and inoculation type, pathogen numbers decreased during storage. The increase of endogenous lactic acid bacteria and the concomitant reduction of pH mostly accounted for this reduction. The inactivation of all three pathogens inoculated into batter or onto slices varied considerably among trials possibly due to variations in the initial batch-to-batch levels of lactic acid microflora and the associated microbial interactions. The effect of structure, composition and microbial interactions on the growth kinetics of L. monocytogenes was evaluated in different growth substrates, including broth, agar, sterile meat blocks, naturally contaminated meat blocks and minced meat. The growth responses of L. monocytogenes were significantly different in the different growth media and food products tested. These differences were more pronounced at low temperatures. The validation of a model based on data from broth against the observed growth of the pathogen in the rest of the tested media showed that broth models may result in significant prediction errors. The potential for mono- or multi-strain cultures of Escherichia coli O157:H7 to attach and form biofilm in combinations of food-contact surfaces, growth substrates and storage temperatures was examined. The susceptibility of biofilms to sanitizers was also evaluated. Attachment and biofilm formation was strain dependent. The presence of food residues (liquid or solid) facilitated the attachment/transfer of E. coli O157:H7 on food-contact surfaces. At moderately cold temperatures culture broth was more conducive to subsequent growth. At chill temperatures the presence of natural microflora in liquid residues enhanced further attachment of the pathogen. Biofilms were less susceptible to sanitation treatments as compared to planktonic cells. Biofilm cells surviving sanitation were able to survive and present slight increases at refrigeration and abuse temperatures, respectively, in cross-contaminated ground meat. Acylated homoserine lactones (AHLs) and autoinducer-2 (AI-2) signalling molecules in the cell-free supernatants of Pseudomonas aeruginosa, Yersinia enterocolitica-like, Serratia proteamaculans and a mixture of two Yersinia enterocolitica strains were found to affect the growth kinetics of two Salmonella Enteritidis and S. Typhimurium strains, respectively. P. aeruginosa synthesized quorum sensing signals that accelerated the metabolic activity of Salmonella strains. All other quorated bacteria tested had a negative effect on both initiation of growth and metabolic activity. The effect seems to be strain and QS signal dependent.